Dielectric Relaxation Dynamics of Clay‐Containing Low‐Density polyethylene Blends and Nanocomposites. Issue 5 (5th February 2020) - Eesaee, Mostafa; David, Eric; Demarquette, Nicole R.
Abstract : Series of clay‐containing nanocomposites have been prepared and investigated using frequency‐domain dielectric spectroscopy at different temperatures. Different matrix materials have been used: neat low‐density polyethylene (LDPE) with and without compatibilizer and co‐continuous blends of LDPE with two grades of polystyrene‐b‐poly(ethylene‐ co ‐butylene)‐b‐polystyrene (SEBS) copolymers. Two major relaxation modes were detected in the dielectric losses of all the nanocomposites and associated with Maxwell–Wagner–Sillars interfacial polarization and dipolar relaxation, respectively. Characteristic relaxation rates, activation energies, dielectric strength, and shape parameters of these relaxation mechanismes were calculated and discussed for the LDPE/clay nanocomposites. The addition of compatibilizer was found to slightly increase the dielectric loss of the nanocomposites while slowing the dynamics due to an improved dispersion. When combined with a high loading of nanofiller (15%), the compatibilizer addition led to low‐frequency dispersion. A new relaxation process was then observed for the nanocomposites with the blend matrix. Several speculations were made as to the origin of this phenomenon, all of which were related to the SEBS phase. POLYM. ENG. SCI., 60:968–978, 2020. © 2020 Society of Plastics Engineers